Sleepers Wake! The Gendered Nature of Sleep Disruption among Mid-life Women - Hislop, J; Arber, S (2003)
This article provides a window onto the gendered nature of our lives through the study of sleep. Drawing on empirical data from focus groups and audio sleep diaries, the article explores sleep from the perspective of mid-life women. It shows that sleep is a socially patterned phenomenon which reflects the gendered nature of women's multiple roles and responsibilities. For many women in mid-life, the reality of sleep is one of disruption, with the bedroom becoming an 'invisible workplace' in which women's sleep needs are compromised by the unpaid physical and emotional labour necessary for the well-being and maintenance of their family. The article suggests that the sleep context may represent a further arena in which gender inequalities are manifest, both in relation to the patterns of women's sleep and in women's responses to sleep disruption.